2019
DOI: 10.1038/s41467-019-09104-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane-cytoskeletal crosstalk mediated by myosin-I regulates adhesion turnover during phagocytosis

Abstract: Phagocytosis of invading pathogens or cellular debris requires a dramatic change in cell shape driven by actin polymerization. For antibody-covered targets, phagocytosis is thought to proceed through the sequential engagement of Fc-receptors on the phagocyte with antibodies on the target surface, leading to the extension and closure of the phagocytic cup around the target. We find that two actin-dependent molecular motors, class 1 myosins myosin 1e and myosin 1f, are specifically localized to Fc-receptor adhes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(92 citation statements)
references
References 91 publications
10
77
0
Order By: Relevance
“…5c and Supplementary Videos 5 & 6, an x-y plane maximum intensity projection of the image data in the volume of the cup showed actin accumulations, spaced ~1.5 µm from each other, at the base of the bead. These podosome-like structures 29 are consistent with observations reported by Barger et al 36 in their study investigating the interplay between myosin-I and actin structure in the phagocytic cup. In the future we will perform 3D correlation analysis to understand the role of these structures in force generation on target cells.…”
Section: Correlation Of Force With Local Actin Dynamicssupporting
confidence: 91%
“…5c and Supplementary Videos 5 & 6, an x-y plane maximum intensity projection of the image data in the volume of the cup showed actin accumulations, spaced ~1.5 µm from each other, at the base of the bead. These podosome-like structures 29 are consistent with observations reported by Barger et al 36 in their study investigating the interplay between myosin-I and actin structure in the phagocytic cup. In the future we will perform 3D correlation analysis to understand the role of these structures in force generation on target cells.…”
Section: Correlation Of Force With Local Actin Dynamicssupporting
confidence: 91%
“…A possible candidate could be the Myosin I family. Indeed, Myosin IE,F,G all connect the membrane to the cytoskeleton, are present at the phagocytic cup and have been shown to participate in target engulfment (Barger et al 2019, Dart et al 2012. Alternatively, the presence of adhesive integrins and podosome-like structures may also contribute to mechano-signaling (Maxson et al 2018, Ostrowski et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…As ERM knockdown HeLa cells do not display the spindle defects or lack of cell rounding 10 , it was suggested that additional cross-linkers play a role in cortical stability in mammalian cells. Class I myosins, including Myo1c, which similarly to ERM proteins connect the plasma membrane to the underlying actin cytoskeleton, are important regulators of membrane tension and cell stiffness in brush border cells, primary mouse fibroblasts and macrophages [45][46][47] . Our observations demonstrate that Myo1c contributes to cortical stiffness of mitotic HeLa; recent studies indicate that effective stiffness is directly related to cortical tension 48,49 .…”
Section: Discussionmentioning
confidence: 99%